2016
DOI: 10.3892/etm.2016.3367
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of combined rituximab treatment in a woman with severe Graves' ophthalmopathy

Abstract: Abstract. The present study reports the case of a female Chinese patient with Graves' disease (GD) and severe Graves' ophthalmopathy (GO) in its active phase, who was treated with propylthiouracil and oral prednisolone for 2 months at a local hospital. However, a lack of improvement in symptoms meant that the patient was transferred to the First Affiliated Hospital of Xi'an Jiaotong University (Xi'an, China), whereupon the patient received high-dose intravenous methylprednisolone pulse therapy, although with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Its immunosuppressive actions are mediated by three mechanisms: reduced activity of B cells as antigen-presenting cells, decreased production of inflammatory cytokines and potential blockage of pathogenic autoantibody generation. 3,6,7 Approved for clinical use in rheumatoid arthritis (RA) and non-Hodgkin's lymphoma, the potential efficacy of RTX has been investigated since 2006 through several uncontrolled studies [7][8][9][10][11][12][13][14][15][16][17][18][19] , and it was assumed that it might become an effective option even as a first-line treatment for GO. 20 In February 2015, two randomised controlled studies, both focused on clinical activity score (CAS), showed contradictory conclusions regarding the efficacy of RTX.…”
Section: Introductionmentioning
confidence: 99%
“…Its immunosuppressive actions are mediated by three mechanisms: reduced activity of B cells as antigen-presenting cells, decreased production of inflammatory cytokines and potential blockage of pathogenic autoantibody generation. 3,6,7 Approved for clinical use in rheumatoid arthritis (RA) and non-Hodgkin's lymphoma, the potential efficacy of RTX has been investigated since 2006 through several uncontrolled studies [7][8][9][10][11][12][13][14][15][16][17][18][19] , and it was assumed that it might become an effective option even as a first-line treatment for GO. 20 In February 2015, two randomised controlled studies, both focused on clinical activity score (CAS), showed contradictory conclusions regarding the efficacy of RTX.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows that 76 articles of the 954 screened records were included in the review. 25–101 The literature on the use of Mabs for treating GO has been centered on blockage of IL-6 (Tocilizumab), 34,39,41,49,50,53,56,58–60,63,64,68–72,79,80,84,87,90,96–98 anti-CD20 lymphocytes (Rituximab), 26–33,35,37,38,40,42–48,51,54,55,61,62,65,67,73,89 and IGF1R (Teprotumumab). 52,66,74–78,82,85,86,88,91,92,94,95,99–101 Three articles have described Mabs that block TNF-α, 25,36,83 and one article has described Mabs that block the B-lymphocyte stimulator (BLyS) protein (Belimumab).…”
Section: Resultsmentioning
confidence: 99%
“…1 shows that 76 articles of the 954 screened records were included in the review. The literature on the use of Mabs for treating GO has been centered on blockage of IL-6 (Tocilizumab), 34,39,41,49,50,53,56,[58][59][60]63,64,[68][69][70][71][72]79,80,84,87,90,[96][97][98] anti-CD20 lymphocytes (Rituximab), [26][27][28][29][30][31][32][33]35,37,38,40,[42][43][44][45][46][47][48]51,54,55,61,62,65,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation